Wisdom and wellbeing in polish older adults: the mediating role of forgiveness - Brudek, Paweł; Steuden, Stanisława; Kaleta, Kinga (Frontiers in Psychology, 2023)
Objectives: Possible correlations between wisdom and well-being among older people have been extensively debated in psychology. At the same time, researchers emphasize that the effect of older adults' wisdom on their well-being depends on numerous mediators. A review of the literature suggests that forgiveness might be one such variable. Thus, the aim of the present study was to investigate whether forgiveness mediated the relationship between wisdom and well-being in late adulthood. Method: Four hundred and eighty one participants aged 60 to 92 (M = 68.84; SD = 6.31) were involved in the study. All older people participating in the study lived independently in their households. Four psychological instruments were used: (1) the Self-Assessed Wisdom Scale; (2) the Heartland Forgiveness Scale; (3) the Psychological Well-Being Scale; and (4) the Satisfaction with Life Scale. Therefore, the measurement of the analyzed variables was self-reported. Results: The results showed that forgiveness mediated the relationships between wisdom and well-being in the older population. The indirect effects demonstrated that forgiveness mediated the relationships between wisdom and well-being. Wisdom related to higher forgiveness (β=.21; p<.01), which in turn was related to a higher level of psychological (β=.48; p<.01) and subjective (β=.36; p<.01) well-being. Conclusion: These findings suggest that forgiveness is an important element of wisdom and well-being. The greater the wisdom the participants showed, the stronger tendency to forgive and the better well-being they reported.